2016
DOI: 10.14419/ijbas.v5i4.6001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an educational program in increasing knowledge and reducing premenstrual syndrome signs, symptoms and severity among nursing college students

Abstract: Objective: The objective of the following study is to determine the effects of an Educational Program in increasing knowledge and reducing premenstrual syndrome symptoms and severity among nursing college students. Material and Methods: A total of 60 students with Premenstrual Syndrome (PMS) symptoms were included in the study group (n=60), the age of the majority of them (75.8%) was between 20-24 years, pre and post education program questionnaire was developed as a tool of data collection before and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
2
3
0
1
Order By: Relevance
“…In a study the applied education program decreased the severity of premenstrual symptoms was reported 32 . In line with the literature, the present study found that the PMSS mean scores of the women in the intervention group decreased after the education compared with the women in the control group.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In a study the applied education program decreased the severity of premenstrual symptoms was reported 32 . In line with the literature, the present study found that the PMSS mean scores of the women in the intervention group decreased after the education compared with the women in the control group.…”
Section: Discussionsupporting
confidence: 91%
“…16,31 In a study the applied education program decreased the severity of premenstrual symptoms was reported. 32 In line with the literature, the present study found that the PMSS mean scores of the women in the intervention group decreased after the education compared with the women in the control group. The result of the present study are similar to in the current literature, which proves the effectiveness of education in coping with premenstrual symptoms even in different designs and different models.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It shows the mean score of students' total knowledge before and after program intervention, the total score before the program was (34.72), while after the program it was (86.28). It's indicated that a significant difference between scores before and after the program was (P=0.000) (Abdalla & Gibreel, 2016).…”
Section: Discussionmentioning
confidence: 98%